2021
DOI: 10.1097/aud.0000000000001147
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Through the Noise: Noise-Induced Cochlear Synaptopathy and Individual Differences in Speech Understanding Among Listeners With Normal Audiograms

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…Based on signal detection theory, Oxenham ( 2016 ) showed that a synapse loss in humans up to 50% may not necessarily translate into measurable effects on behavioral tasks. Furthermore, the different behavioral tools used in human CS studies place variable sensory, perceptual, and central/cognitive demands (such as attention and memory), which likely contribute to inter-subject variability (Bramhall et al, 2019 ; DiNino et al, 2022 ). Thirdly, noise-induced CS in humans might not preferentially impair low- to medium-SR ANFs (as discussed in Section Histopathological and Neurophysiological Aspects: Noise Exposure).…”
Section: Behavioral Proxy Measures In Humansmentioning
confidence: 99%
“…Based on signal detection theory, Oxenham ( 2016 ) showed that a synapse loss in humans up to 50% may not necessarily translate into measurable effects on behavioral tasks. Furthermore, the different behavioral tools used in human CS studies place variable sensory, perceptual, and central/cognitive demands (such as attention and memory), which likely contribute to inter-subject variability (Bramhall et al, 2019 ; DiNino et al, 2022 ). Thirdly, noise-induced CS in humans might not preferentially impair low- to medium-SR ANFs (as discussed in Section Histopathological and Neurophysiological Aspects: Noise Exposure).…”
Section: Behavioral Proxy Measures In Humansmentioning
confidence: 99%
“…This is because in general factory workers in China have a lower educational level (Chen and Guan, 2016). It has been previously reported that both cognitive resources and language competence can influence SPiN performance (Schneider et al, 2002;Pienkowski, 2017;DiNino et al, 2022). These aspects were not explored in the present study, and thus, we cannot conclude that sensory processing was the main underlying factor that explained our results.…”
Section: Speech Perception In Noisementioning
confidence: 54%
“…Overall, although the relationship between physiological correlates of cochlear deafferentation and speech perception measures were not consistent across all studies, those that used speech perception measures with some of the features suggested by DiNino et al (2022) , used EFR with a RAM stimulus or wideband MEMR as the physiological measure, and/or included populations at high risk for synaptopathy (due to age or military noise exposure) tended to find that weaker physiological measurements were associated with poorer speech perception performance. It is possible that this relationship is non-linear and that the negative impacts of cochlear deafferentation on speech perception only become evident when a particular threshold level of deafferentation is reached.…”
Section: Perceptual Consequences Of Cochlear Deafferentation In Human...mentioning
confidence: 90%
“…It's possible that the sensitivity to cochlear deafferentation-related speech perception deficits may differ depending on the speech perception measure used. DiNino et al (2022) proposed that the ideal speech perception measure for capturing cochlear deafferentation-related deficits would possess four features; it would be appropriately difficult for adults with normal hearing thresholds; it would have limited contextual, semantic, and syntactic content; it would emphasize temporal processing (e.g., by using time compression or reverberation); and it would allow competing speech streams to be differentiated only by fine spatial cues (rather than based on fundamental frequency). They found that previous studies that showed evidence of a relationship between a physiological correlate of cochlear deafferentation and speech perception performance included a speech perception metric with one or more of these features.…”
Section: Perceptual Consequences Of Cochlear Deafferentation In Human...mentioning
confidence: 99%